SARS-CoV-2 triggers pericyte-mediated cerebral capillary constriction - Hirunpattarasilp, C; James, G; Kwanthongdee, J; Freitas, F; Huo, J; Sethi, H; Kittler, JT; Owens, RJ; McCoy, LE; Attwell, D (Oxford University Press, 2022)
The SARS-CoV-2 receptor, ACE2, is found on pericytes, contractile cells enwrapping capillaries that regulate brain, heart and kidney blood flow. ACE2 converts vasoconstricting angiotensin II into vasodilating angiotensin-(1-7). In brain slices from hamster, which has an ACE2 sequence similar to human ACE2, angiotensin II evoked a small pericyte-mediated capillary constriction via AT1 receptors, but evoked a large constriction when the SARS-CoV-2 receptor binding domain (RBD, original Wuhan variant) was present. A mutated non-binding RBD did not potentiate constriction. A similar RBD-potentiated capillary constriction occurred in human cortical slices, and was evoked in hamster brain slices by pseudotyped virions expressing SARS-CoV-2 spike protein. This constriction reflects an RBD-induced decrease in the conversion of angiotensin II to angiotensin-(1-7) mediated by removal of ACE2 from the cell surface membrane and was mimicked by blocking ACE2. The clinically used drug losartan inhibited the RBD-potentiated constriction. Thus, AT1 receptor blockers could be protective in COVID-19 by preventing pericyte-mediated blood flow reductions in the brain, and perhaps the heart and kidney.